Investigation of quantum and thermal fluctuations ferromagnetic spin chains with easy-plane anisotropy. (28th May 2019) - Wieser, R
Abstract: One-dimensional ferromagnetic S = 1/2 and S = 1 spin chains with easy-plane and easy-axis exchange anisotropy are studied by the double-time Green's function method. The XYZ model can be used to describe several chain systems as the ferromagnetic spin chain of (CHAB). Alternatively, ferromagnetic spin-spirals with Dzyaloshinsky–Moriya interaction. To study quantum and thermal fluctuations the magnetization and susceptibility are calculated and analyzed as a function of the external field, the strength of the anisotropy and the chain length.